2005
DOI: 10.1183/09031936.05.00010405
|View full text |Cite
|
Sign up to set email alerts
|

Normal values for respiratory resistance using forced oscillation in subjects >65 years old

Abstract: The aim of the present study was to determine reference values and predictive variables for respiratory impedance (Zrs) by the forced oscillation technique (FOT) in subjects aged .65 yrs.The investigation involved a prospective study of nonsmoking subjects, with normal forced expiratory volumes. The Zrs parameters, which included average resistance between 4-16 Hz (R4-16), average resistance between 4-30 Hz (RM), resonant frequency (FN), capacitance (C) and inertance (I), were measured along with forced expira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
5
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 29 publications
5
41
5
1
Order By: Relevance
“…In contrast, there have been only a few reports on normative respiratory impedance (Zrs) data in healthy adults, and some involved only relatively young or only elderly subjects [3,4], or only a small number of oscillation frequencies were investigated [5]. Moreover, the criteria for selection of the subjects were not always reported or the sample population was limited to a rather narrow specific subgroup of subjects [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there have been only a few reports on normative respiratory impedance (Zrs) data in healthy adults, and some involved only relatively young or only elderly subjects [3,4], or only a small number of oscillation frequencies were investigated [5]. Moreover, the criteria for selection of the subjects were not always reported or the sample population was limited to a rather narrow specific subgroup of subjects [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Some reference values for Rrs have been developed for healthy children and for adults aged up to 70 yrs [10]. In the present issue of the European Respiratory Journal, GUO et al [1] report values of Rrs in a large group of 223 healthy, nonsmoking subjects aged 65-100 yrs (mean age 83 yrs). They found that: 1) Rrs was slightly lower in aged subjects than previously reported in younger adults; 2) Rrs was higher in females (the majority of subjects) than males; and 3) Rrs was inversely related to height.…”
mentioning
confidence: 99%
“…A practical problem in assessing results of spirometry in older subjects is that often reference values have been derived by linear extrapolation of decline rates from studies with few subjects aged .70 yrs [1], thus, ignoring any acceleration in the rate of decline in FEV1 that occurs with increasing age [13]. Fortunately, in the past 10 yrs several studies have reported reference values from data sets which included reasonable numbers of aged subjects up to 80-85 yrs of age [14][15][16][17][18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased R max , rs in ARDS patients has been previously described [20,23] and attributed to decreased lung volume and time-constant inequalities [22,24]. In elderly subjects R max , rs have been described to be normal [25] or slightly decreased [26]. Although small airways closure has been associated with the decrease in maximal expiratory flow observed in elderly patients [27,28], this phenomenon is not expected to affect Rmax, rs since peripheral airways make a relatively small contribution to the total resistance of the respiratory system [29].…”
Section: Discussionmentioning
confidence: 99%